CP-MAS and Solution NMR Studies of Allosteric Communication in CA-assemblies of HIV-1. Issue 16 (30th August 2022) - Nicastro, Giuseppe; Lucci, Massimo; Oregioni, Alain; Kelly, Geoff; Frenkiel, Tom A.; Taylor, Ian A.
Graphical abstract: Highlights: CP-MAS NMR measurement of HIV CA-assembly - ligand complexes. NMR observations of dynamic allostery in HIV-CA assemblies. Crystal structure of CA-IP6-CPSF6 ternary complex. Solution NMR measurement of ligand-binding induced CA dynamics. Abstract: Solution and solid-state NMR spectroscopy are highly complementary techniques for studying structure and dynamics in very high molecular weight systems. Here we have analysed the dynamics of HIV-1 capsid (CA) assemblies in presence of the cofactors IP6 and ATPγS and the host-factor CPSF6 using a combination of solution state and cross polarisation magic angle spinning (CP-MAS) solid-state NMR. In particular, dynamical effects on ns to µs and µs to ms timescales are observed revealing diverse motions in assembled CA. Using CP-MAS NMR, we exploited the sensitivity of the amide/Cα-Cβ backbone chemical shifts in DARR and NCA spectra to observe the plasticity of the HIV-1 CA tubular assemblies and also map the binding of cofactors and the dynamics of cofactor-CA complexes. In solution, we measured how the addition of host- and co-factors to CA -hexamers perturbed the chemical shifts and relaxation properties of CA-Ile and -Met methyl groups using transverse-relaxation-optimized NMR spectroscopy to exploit the sensitivity of methyl groups as probes in high-molecular weight proteins. These data show how dynamics of the CA protein assembly over a range of spatial and temporal scales play a critical role in CA function. Moreover, we show that binding of IP6, ATPγS and CPSF6 results in local chemical shift as well as dynamic changes for a significant, contiguous portion of CA, highlighting how allosteric pathways communicate ligand interactions between adjacent CA protomers.